Asthma control, cost and race: results from a national survey. (12th June 2013) - Gold, Laura S.; Yeung, Kai; Smith, Nancy; Allen-Ramey, Felicia C.; Nathan, Robert A.; Sullivan, Sean D.
Abstract: Objective : Although interventions have been shown to alleviate symptoms in most patients suffering from asthma, only one-third of asthma patients have disease that is well-controlled. The purpose of this study is to investigate whether partly and uncontrolled asthmas are associated with increased costs for asthma-related healthcare utilization compared to well-controlled asthma and to determine whether these associations differed across racial groups. Methods : We classified respondents from the Asthma Insights and Management survey into those with well-, partly and uncontrolled asthma and compared utilization of healthcare services and costs among these groups, as well as between whites and non-whites. Results : Respondents categorized as having asthma that was not well-controlled reported lower income levels, higher rates of unemployment and more trouble paying for healthcare; similar results were found in analyses stratified by race. Patients whose asthma was partly or uncontrolled had greater use of asthma-related medications and medical services compared to patients whose asthma was well-controlled. Total unadjusted and adjusted costs were greater in patients whose asthma was classified as partly and uncontrolled. Similar results were found in analyses stratified on race. Across all levels of asthma control, non-whites had higher rates of utilization of emergency rooms and urgent care facilities and had greater rates of hospitalizations compared to whites. Conclusions : Our findings indicate that patients with asthma that is not well-controlled utilized more healthcare resources and had greater medical costs, despite lacking of health insurance which may suggest less access to care.